Public-private partnerships policy and practice : a reference guide - Yong, H. K. (Commonwealth Secretariat LondonGB, 2010)
Provides a comprehensive reference manual on public-private sector partnership (PPP) theory and practice for senior policy-makers and other public sector officials in developing countries. Focuses on the key lessons learnt and emerging best practices from successful and failed PPP transactions over the past thirty years.